The Application of Acceptance Commitment Therapy (ACT) and Family Psychoeducation (FPE) to Clients with Scizophrenia and Aggressive Behavior - Buanasari, Andi; Keliat, Budi Anna; Susanti, Herni (Department of Nursing, Faculty of Medicine, Diponegoro University, 2020)
Background: Aggressive behavior frequently occurs in clients with schizophrenia and causes injuries to the clients themselves, others, and the environment. It becomes one of the most common factors causing rehospitalization in schizophrenic clients. Aggressive behavior can be managed by the intervention administered by nurses in the usual way (treatment as usual; TAU) as well as psychotherapy (acceptance and commitment therapy; ACT and family psychoeducation; FPE).Purpose: This study aimed to investigate the effectiveness of acceptance and commitment therapy (ACT) and family psychoeducation (FPE) on schizophrenic clients with aggressive behavior.Methods: This study used a case series method to report four selected cases of schizophrenic clients with aggressive behavior. Acceptance and commitment therapy (ACT), family psychoeducation (FPE), and treatment as usual (TAU) were delivered to four clients with aggressive behavior for six weeks using the Stuart Stress-Adaptation Model.Results: The finding showed decreased symptoms of aggressive behavior in cognitive, affective, physiological, behavioral, and social aspects and increased ability to control anger, to accept their problems, and to commit to the therapy after ACT, FPE, and TAU interventions.Conclusion: This report showed that TAU, ACT, and FPE effectively decreased the symptoms of aggressive behavior and increased the clients’ ability to control anger.